Policy Formulation of Fraud Offenses in the New Penal Code Concept for Combating Technology-Related Crimes: Kebijakan Formulasi Tindak Pidana Penipuan dalam Konsep KUHP Baru untuk Menanggulangi Kejahatan di Bidang Teknologi - Wahid, Abdul (Rechtsidee, 2023)
This study critically analyzes the formulation of criminal offenses related to fraud in the revised Penal Code (KUHP) within the context of contemporary technological advancements. Employing a normative legal research method, the investigation draws on relevant legal literature, legislation, and scholarly publications. The findings reveal inadequacies in the current legal provisions, particularly in addressing cyber fraud facilitated by information technology. The newly introduced Article 492 of the revised KUHP remains rooted in conventional fraud models, lacking the capacity to accommodate digital modus operandi and failing to encompass diverse identity theft techniques and system vulnerabilities. The absence of specific regulations pertaining to electronic transactions, computer networks, and digital systems further underscores the limitations. While the revised KUHP exhibits positive enhancements, urgent revisions are warranted to incorporate comprehensive elements, impose stricter penalties, and reinforce global cooperation in combating cybercrime. The overarching goal is to ensure that criminal provisions remain adaptive and responsive to the dynamic landscape of technology-driven offenses in the future. Highlights: The revised Penal Code inadequately addresses digital fraud, necessitating a comprehensive update to encompass evolving technological modus operandi. Existing legal provisions lack specificity concerning electronic transactions, computer networks, and digital systems, revealing a crucial gap in addressing contemporary cyber threats. Urgent revisions are imperative to fortify criminal statutes, impose stricter penalties, and enhance international collaboration, ensuring a responsive legal framework for combating future technology-based crimes. Keywords: Technological Fraud, Penal Code Revision, Cybercrime Legislation, Legal Adaptation, Global Cooperation